Motif Ekonomi Etnis Karo di Kawasan Sekitar Universitas Sumatera Utara - Muhammad Adenan Ginting; Badaruddin Badaruddin; Zulkifli Lubis (PERSPEKTIF, 2020)
This study aims to see the economic motives of the Karo ethnic group in developing and surviving in the USU region. This type of research uses a qualitative approach, the research location is in Jalan Jamin Ginting Medan or specifically in the Padang Bulan area, precisely from the campus intersection to the Harmonika Road intersection and the Road Development area to the Kampung Susuk intersection. Taking this location is intended to be more detailed and specific to see how the existence of USU becomes a central point for Ethnic Karo to adapt to follow development by mingling in the provision of student needs. The results showed that the motives that influenced the ethnic karo to survive were the land they owned as an inheritance and believed that the land had a living spirit (ertendi); strategic land with the existence of USU as the main attraction of their business. the motive influencing the ethnic karo to develop is to look at the short-term opportunities of their efforts to just survive, only see the opportunities available and only be able to provide the needs of students in accordance with the times. The conclusion from the iani research is that the Karo Ethnic survive in the area around the University of Sumatra because they have strong motives in themselves, how they maintain their assets. Karo ethnic develops because of the opportunities presented. A character that is found in the field of how ethnic karo who love to gamble with luck is implemented in the way they see business opportunities. USU as an opportunity was recognized as their way to reap profits and develop businesses.